A Survey of Incipient Fault Diagnosis of Bearings Based on Data-drive - Li Zhaofei (Jixie chuandong)
On-line real time diagnosis of bearing incipient faults is the intersection of practical engineering application requirements and basic scientific research. It is one of the development directions of bearing fault diagnosis at home and abroad. Firstly, this study analyzes the bearing fault and its evolution process; secondly, according to the needs of bearing incipient fault diagnosis in time, the difficult problems of bearing incipient fault diagnosis are summarized; then, it focuses on the various technologies used in the three crucial links of bearing early fault diagnosis: the weak monitoring signal enhancement technology, the fusion representation technology of monitoring parameters and the early fault intelligent diagnosis technology; finally, the development trend of bearing incipient fault diagnosis technology is summarized and prospected.